DEPENDENCE OF PHOTONIC BAND GAP ON THE RADIUS OF TRACES IN TiO2 NANOSTRUCTURES (2017)
We study the evolution of the photonic gap present in TiO2 traces, these structures appear in the Ti-TiO2 interface during titania nanotubes formation. Traces can be modeled like photonic crystal because the dielectric function varies periodically in a bi-dimensional space. We conducted a theoretical study based on experimental measurements in traces of TiO2. The study was developed using a plane wave expansion method. This work is a first attempt to introduce photonic gap engineering, which could have technological interests.